Things that matter: Adolescent and young adult patients' priorities during cancer care. Issue 9 (17th June 2019) - Graetz, Dylan; Fasciano, Karen; Rodriguez‐Galindo, Carlos; Block, Susan D.; Mack, Jennifer W.
Abstract: Background: Adolescents and young adults (AYAs) experience cancer while balancing emerging identity and life goals. We investigated AYAs' priorities during cancer, including psychosocial concerns, cure‐directed therapy, and potential late effects. Methods: We surveyed 203 cancer patients aged 15–29 treated at Dana‐Farber Cancer Institute, Boston, Massachusetts, and their oncologists. Patients were approached and rated the importance of aspects of treatment, outcomes, and life during therapy. Response options were "extremely, " "very, " "somewhat, " "a little important, " or "not at all important." Ratings of "extremely" or "very important" were used as indicators of strong priorities. Results: Patients' three most frequent priorities were cure (97%), being good to the people they care about (95%), and having supportive people around them (94%). Most prioritized being with family (90%), returning to school/work (89%), maintaining relationships with friends (88%), and feeling normal (85%). Fewer prioritized minimizing long‐term (78%) and acute side effects (68%) and fertility (59%). Many participants (88%) said that cure influenced their decisions "a great deal, " while fewer were influenced by side effects (32%), fertility (36%), or relationships (16%). Most patients (85%) thought their oncologist understood what was most important to them when treatment started. Conclusion: Nearly all AYA cancer patients prioritize cure, while maintaining social relationships and a sense of normalcy. These priorities influence decisions they make about treatment to differing degrees, with cure influencing decision‐making for most patients. Although the priority of cure is well established, recognizing other AYA priorities allows providers to optimally support these patients from the time of diagnosis.